Legality Camat And Lurah In Publishing Land Administration In Medan City - Batubara, Hirsan; Luis, Rafnila; Vincen, Vincen; Sitompul, Ariman (Universitas Dharmawangsa, 2024)
In carrying out land registration, Head of Land Office assisted by PPAT and other officials assigned to carry out certain activities according to Government regulations and legislation (Government Regulation No. 24 Year 1997 article 6 paragraph 2). What other officials mean in implementing land registration according to Government Regulation Number: 24 of 1997 article 6 paragraph 2 is the official Government that controls the state of the area concerned (village heads, Village Heads and Camat). One of the policies taken by the government to serve and meet community needs in making PPAT deed in areas where there is not enough PPAT or to serve certain groups of people in making certain PPAT deed then the minister appoints regional officials as temporary PPAT or special PPAT. Lurah dan Camat appointed to serve the creation of the deed in areas that have not enough PPAT as a temporary patch. In accordance with Government Regulation Number: 24 of 2016 on Regulation PPAT, Lurah and Camat as government officials at the level bottom has an important role in supporting the achievement of legal certainty land rights in land registration activities. The role of the headman and Sub-Head is considered very influential to increase ownership of land rights at the district level. The purpose of this study is to identify the legality of the role of Lurah and Camat as a temporary land deed officer at the district level. This research using empirical and normative methods. Data collection techniques that the authors use is the author's experience and literature research. Data analysis techniques used is data collection, data presentation and conclusion.